Performance comparisons of AOMDV and OLSR routing protocols for mobile ad hoc network - Oo, M.Z.; Othman, M. (2010)
A Mobile Ad Hoc Network (MANET) eliminates the complexity of an infrastructured configuration and allows wireless devices to communicate with each other on the fly for any application. It does not rely on a base station to coordinate the flow of messages to nodes in the network. A primary challenge is for each device to maintain the information to properly route traffic and data packets. In this paper, we analyze the performance differences of Ad hoc On-demand Multi-path Distance Vector (AOMDV) and Optimized Link State Routing (OLSR) routing protocols. We evaluate their performance through simulation using network simulator (ns- 2). We analyse the strengths and weaknesses of these two protocols by measuring packet loss rates (%), average end to end delay (sec), and normalized routing load.